Mitochondrial chaperon TNF-receptor- associated protein 1 as a novel apoptotic regulator conferring susceptibility to Pneumocystis jirovecii pneumonia - Amali, Aseervatham Anusha; Paramasivam, Kathirvel; Huang, Chiung Hui; Joshi, Abhinav; Hirpara, Jayshree L.; Ravikumar, Sharada; Sam, Qi Hui; Tan, Rachel Ying Min; Tan, Zhaohong; Kumar, Dilip; Neckers, Leonard M.; Pervaiz, Shazib; et al. (Frontiers in Immunology, 2024)
Molecular chaperons stabilize protein folding and play a vital role in maintaining tissue homeostasis. To this intent, mitochondrial molecular chaperon may be involved in the regulation of oxidative phosphorylation and apoptosis during stress events like infections. However, specific human infectious diseases relatable to defects in molecular chaperon have yet to be identified. To this end, we performed whole exome sequencing and functional immune assessment in a previously healthy Asian female, who experienced severe respiratory failure due to Pneumocystis jiroveci pneumonia and non-HIV-related CD4 lymphocytopenia. This revealed that a chaperon, the mitochondrial paralog of HSP90, TRAP1, may have been involved in the patient’s susceptibility to an opportunistic infection. Two rare heterozygous variants in TRAP1, E93Q and A64T were detected. The patient’s PBMC displayed diminished TRAP1 expression, but had increased active, cleaved caspase-3, caspase-7 and elevated IL-1β production. Transfection of A64T and E93Q variants in cell lines yielded decreased TRAP1 compared to transfected wildtype TRAP1, and re-capitulated the immunotypic phenotype of enhanced caspase-3 and caspase-7 activity. When infected with live P. jiroveci, the E93Q or A64T TRAP1 mutant expressing cells also exhibited reduced viability. Patient cells and cell lines transfected with the TRAP1 E93Q/A64T mutants had impaired respiration, glycolysis, and increased ROS production. Of note, co-expression of E93Q/A64T double mutants caused more functional aberration than either mutant singly. Taken together, our study uncovered a previously unrecognised role of TRAP1 in CD4+ lymphocytopenia, conferring susceptibility to opportunistic infections.